2017
DOI: 10.3233/jad-160898
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Drugs Screening System Reveals that Baicalein Ameliorates the Aβ/AMPA/NMDA-Induced Depolarization of Neurons

Abstract: The presence of amyloid-β (Aβ) plaque and tau protein hyperphosphorylation in brain tissue is the pathological hallmark of Alzheimer's disease (AD). At least some Aβ neurotoxicity is caused by the presence of excess glutamate that has been induced by Aβ accumulation. Memantine is currently the only NMDA receptor inhibitor approved for treating moderate-to-severe AD patients. We utilized primary cortical neurons and DiBAC4(3), a slow-response voltage sensitive fluorescence dye, to create a novel system for scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Neurodegeneration induced by NMDAR hypoactivity was also proposed to contribute to AD and to be related to the progression of aging brain from mild cognitive impairment to AD (Olney et al, 1997 ; Wozniak et al, 1998 ). Compared to healthy individuals, the serum levels of DAAO are increased in patients affected by mild cognitive impairment and mild and severe AD (Lin et al, 2017 ), and DAAO levels correlate with the severity of cognitive deficit and with the D-serine level.…”
Section: Role Of Daao In Physiological and Pathological Conditionsmentioning
confidence: 99%
“…Neurodegeneration induced by NMDAR hypoactivity was also proposed to contribute to AD and to be related to the progression of aging brain from mild cognitive impairment to AD (Olney et al, 1997 ; Wozniak et al, 1998 ). Compared to healthy individuals, the serum levels of DAAO are increased in patients affected by mild cognitive impairment and mild and severe AD (Lin et al, 2017 ), and DAAO levels correlate with the severity of cognitive deficit and with the D-serine level.…”
Section: Role Of Daao In Physiological and Pathological Conditionsmentioning
confidence: 99%
“…Baicalein also showed neuroprotective effects on excitotoxic neuronal cell death in primary rat cortical cell cultures (Yang et al, 2014). Interestingly, an improved drugs screening system revealed that baicalein not only ameliorates the Aβ-induced depolarization of neurons, but also possibly functions as an antagonist of AMPA and NMDA receptors (Lin et al, 2017). In rat hippocampal nerve terminals (synaptosomes), baicalein inhibits depolarization-induced glutamate release, while in slice preparations whole cell patch-clamp experiments revealed that baicalein reduced the frequency of miniature excitatory postsynaptic currents without affecting their amplitude.…”
Section: Baicalein Inhibits Excitotoxicitymentioning
confidence: 99%
“…Baicalein has a wide safety margin and appears to be able to permeate the blood-brain barrier (BBB) (Chen et al, 2016;Liu et al, 2010;Tsai et al, 2002). Several in vitro studies have shown that baicalein is effective in preventing neurotoxicity induced by a variety of neurotoxins and stress inducers, including Aβ (Lin et al, 2017;Wang et al, 2004), 6-hydroxydopamine (6-OHDA) (Lee et al, 2005), rotenone (Li et al, 2012),H2O2 (Zhang et al, 2010), and glutamate (Lee et al, 2003), and others. In recent studies, moreover, baicalein has been shown to possess neuroprotective properties in several animal models of AD and PD (Cheng et al, 2008;Gao et al, 2015;Gu et al, 2016;Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Supporting this idea, D-Ser was shown to exert a neuroprotective effect against apoptosis, promoting neuronal survival (Esposito et al, 2012 ) and the DAAO competitive inhibitor sodium benzoate was found to ameliorate cognitive and overall function in patients with early phase AD (Lin et al, 2014 ). Furthermore, recently increased levels of DAAO have been reported in the serum of mild cognitive impairment patients, as well as mild and severe AD patients, compared to healthy individual (Lin et al, 2017 ). Worthy of note, the flavoenzyme levels increased with the severity of cognitive deficit and were significantly associated with D-Ser serum content.…”
Section: Daao and Pathologies: Proposed Roles And Implicationsmentioning
confidence: 99%